2017
DOI: 10.1097/bsd.0000000000000459
|View full text |Cite
|
Sign up to set email alerts
|

The Utility of Routinely Obtaining Postoperative Laboratory Studies Following a Minimally Invasive Transforaminal Lumbar Interbody Fusion

Abstract: Level III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Of the 31 articles, 26 articles specified the complications following MI-TLIF (Table 1). There were five articles that met inclusion criteria but did not report complications [35][36][37][38][39]. The most common complication cited after MI-TLIF surgery was radiculitis, with a range between rates of 2.8 and 57.1%.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 31 articles, 26 articles specified the complications following MI-TLIF (Table 1). There were five articles that met inclusion criteria but did not report complications [35][36][37][38][39]. The most common complication cited after MI-TLIF surgery was radiculitis, with a range between rates of 2.8 and 57.1%.…”
Section: Resultsmentioning
confidence: 99%
“…Although previous protocols in medical and surgical services have demonstrated success in reducing unnecessary laboratory testing, most interventions have been focused on increasing provider awareness, eliminating automatic order sets, and implementing universal guidelines. 2,5,8,9 Some programs implemented for high-risk patients in postoperative care units have attempted to consider adjusting ordering patterns based on patient comorbidities and clinical status, yet decision-making is typically based on provider opinion or consensus without a specific tool to risk stratify patients into appropriate laboratory testing tiers. [26][27][28] This study therefore represents a new implementation of predictive analytics to guide a laboratory costreducing protocol in a patient-centered model.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 Multiple studies have demonstrated reduction in laboratory testing and associated costs after implementing protocols for different patient populations; however, these systems are almost universally applied to an entire cohort of patients without targeted risk assessment to determine a subset of patients who could appropriately receive a limited-laboratory protocol. 2,5,8,9 The explosion of predictive analytical tools for clinical outcomes has suggested its expansion to improve economic outcomes by associating patient risk with resource allocation. 10 Unfortunately, this application remains underexplored and specifically has not been applied to routine postoperative laboratory testing.…”
mentioning
confidence: 99%
“…7 This is partly due to the perception that outpatient spine surgeries are less costly than similar inpatient procedures. 2,7 With the increasing scrutiny of health expenditures, the perceived cost savings and comparable outcomes to inpatient procedures have made outpatient spine procedures desirable for payers and surgeons. 3 Several studies have looked at patient selection and selected outcomes for specific spine surgical procedures, yet no review exists that examines the common patient selection factors and outcomes across the portfolio of outpatient spinal procedures.…”
mentioning
confidence: 99%